English and the vernacular as media in teaching arithmetic in the elementary grades - Soberano, Editha Mulata (Education quarterly.)
Vernacular as medium of classroom instruction for the teaching of fractions in the program of modern mathematics did not show any advantage over the English language. However in the discovery of formula for geometrical measurements, vernacular helped the pupils of low abilities in better understanding and in solving of practical problems.